2022
DOI: 10.3389/fnut.2022.961875
|View full text |Cite
|
Sign up to set email alerts
|

Pectin Stabilized Fish Gelatin Emulsions: Physical Stability, Rheological, and Interaction Properties

Abstract: Pectin, a kind of natural polysaccharide, shows the attractive potential as a natural stabilizer for protein emulsion. The aim of this study is to investigate the effect of pectin on the physical stability, rheology, interface, and interaction properties of the fish gelatin (FG) emulsion, as pectin was utilized to improve the stability of FG, fish oil emulsion. During the study, when pH < 6, the FG-pectin emulsion displayed better storage stability and salinity tolerance. Analyzing the result, pectin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Similar research on fish oil gelatin emulsions also reported this steric stabilization effect when adding pectin to the systems to form double‐layered emulsions. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar research on fish oil gelatin emulsions also reported this steric stabilization effect when adding pectin to the systems to form double‐layered emulsions. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
“…emulsions also reported this steric stabilization effect when adding pectin to the systems to form double-layered emulsions. [30] CO oxidative stability during emulsification processes was also checked. Figure 2 presents PV and TBARS of CO before and after each emulsification step: ultra-turrax and ultrasound.…”
Section: Characterization Of Emulsions and Wpi-hpm Double-layered For...mentioning
confidence: 99%
“…FG–gum arabic interaction led to an increase in the stability of the emulsion gel ( 20 ). Pectin improved the physical stability and rheological properties of FG emulsions ( 21 ). TGase-modified FG increased the creaming stability of fish oil-loaded emulsions ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…[34]. Pectin has been incorporated into emulsions or nanoemulsions in numerous works [35][36][37] to provide structure or stability to the sample, but it should be noted that pectin was added as a powder or in solution, not in the form of a gel. Really, there are a few works that use pectin as a gelled matrix for the preparation of an emulgel, as occurs in this investigation.…”
Section: Introductionmentioning
confidence: 99%